Entrepreneurship training and mentoring for the Marsudi Luhur women farmer group - Sunarta, Sunarta; Aryanto, Ardi; Utami, Zuchdiawati Luthfi; Dias, Bartolomius; Saputra, Viant Anggi; Arifin, Noor; Ramadhan, Aditiya Akbar; Lestari, Wiwit; Addiba, Mutiara Zakya; Bilqisthy, Syena Azkiya (Universitas Negeri Yogyakarta, 2026)
This community service program aimed to enhance the entrepreneurial capacity of Marsudi Luhur Women Farmer Group (KWT) through training and mentoring focused on improving entrepreneurial skills, expanding marketing reach, and fostering sustainable entrepreneurial motivation. The program employed a participatory training and mentoring approach comprising four main components: mindset transformation, entrepreneurial spirit building, business environment awareness, and promotional media selection. Program effectiveness was evaluated through pretest and posttest with statistical analysis using Paired Samples T-Test. The results showed a highly significant improvement (p < 0.001) with an average score increase from 8.44 to 9.56. There was also a homogenization of participants' understanding indicated by the decrease in standard deviation from 1.261 to 0.586. The training and mentoring program proved effective in enhancing the entrepreneurial capacity of KWT members. For sustainability, follow-up mentoring focusing on digital marketing and product development is recommended.